g(x) = - log(x) + 2
Description of transformation:
Equation(s) for the vertical asymptote(s):
x-intercept in (x,y) form:
The line does not cross over the x-axis so I'm lost with this problem; need help.
g(x) = - log(x) + 2
Description of transformation:
Equation(s) for the vertical asymptote(s):
x-intercept in (x,y) form:
The line does not cross over the x-axis so I'm lost with this problem; need help.
1) Flip f(x) = g(x) about x-axis to get y1 = -log(x). Move y1 = -log(x) up by 2 units to get g(x) = - log(x) + 2.
2) x = 0, since when x-->0, y-->-oo.
3) x-intercept is at (100, 0), since -log(100) + 2 = 0, if the base is 10.